2003
DOI: 10.1046/j.1432-1033.2003.03795.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and molecular cloning of tyrosinase from the cephalopod mollusk, Illex argentinus

Abstract: Tyrosinase (monophenol, L-DOPA:oxygen oxidoreductase) was isolated from the ink of the squid, Illex argentinus. Squid tyrosinase, termed ST94, was found to occur as a covalently linked homodimeric protein with a molecular mass of 140.2 kDa containing two copper atoms per a subunit. The tyrosinase activity of ST94 was enhanced by proteolysis with trypsin to form a protein, termed ST94t, with a molecular mass of 127.6 kDa. The amino acid sequence of the subunit was deduced from N-terminal amino acid sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 54 publications
(93 reference statements)
1
27
0
Order By: Relevance
“…These results indicated that the Octopus proPO was a heterodimeric protein of 153.8 kDa with two subunits of 75.6 and 73 kDa. The dimeric property of the Octopus proPO was similar with that of tyrosinase from squid Illex argentinus, which was found to occur as a covalently linked homodimeric protein with a molecular mass of 140.2 kDa [28].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These results indicated that the Octopus proPO was a heterodimeric protein of 153.8 kDa with two subunits of 75.6 and 73 kDa. The dimeric property of the Octopus proPO was similar with that of tyrosinase from squid Illex argentinus, which was found to occur as a covalently linked homodimeric protein with a molecular mass of 140.2 kDa [28].…”
Section: Discussionmentioning
confidence: 75%
“…The optimal pH of purified Octopus PO was 7.0 against L-DOPA which was similar to that of Ruditapes philippinarum [17] and colonial ascidian Botryllus schlosseri ( pH 7.0-7.5) [29], higher than that of P. chinensis ( pH 6.0) [16] and Charybdis japonica ( pH 6.0) [18], and lower than that of Penaeus setiferus ( pH 7.5) [30], Illex argentinus ( pH 8.0) [28], brown shrimp ( pH 8.0) [22], and Heliothis virescens ( pH 9.5) [31]. The purified Octopus PO had an optimum temperature of 408C coinciding with that of Japanese prawn [32], P. chinensis [16], C. japonica [18], and R. philippinarum [17], higher than that of Drosophila melanogaster (308C) [33], and lower than that of Chlamys farreri (458C) [34] and P. setiferus (458C) [30].…”
Section: Discussionmentioning
confidence: 76%
“…The squid ink has been reported to have anti-radiation activity, antitumor activity, immunomodulatory activity, procoagulant function and so on (Takaya 2000). Several bioactive molecules, including a glycosaminoglycan like polysaccharides (Chen et al 2008), a tyrosinase (Naraoka et al 2003) and an angiotensin-converting enzyme inhibitor (Kim et al 2003) have been identified from squid ink. Among them, the melanin has attracted most research interests.…”
Section: Introductionmentioning
confidence: 99%
“…ProPO can readily be activated to PO by both an endogenous activating system and exogenous activators such as trypsin, lipopolysaccharide and zymosan (b-1,3-glucan) [1,11e14]. It has been shown that the proPO system, comprising proPO together with its activating enzyme, plays a role in defence reactions, including melanisation [15], sclerotisation [16], encapsulation [17e19] and wound healing [20], in both arthropods and molluscs [21,22]. In addition, the proPO system is also involved in several physiological processes such as neurotransmitter synthesis, eye pigmentation and production of inks [23e26].…”
Section: Introductionmentioning
confidence: 99%
“…However, quite a few problems such as its instability, ''stickiness'' and loss of activity during purification have prevented the detailed characterisation of PO, and it has thus far been purified only from arthropods [11,13,14,27e31], molluscs [21] and ascidians [23]. Consequently, knowledge of the biochemical properties of this enzyme is very limited.…”
Section: Introductionmentioning
confidence: 99%